Coexisting genital malignancies with tuberculosis: A case series with review of literature - Avantika Gupta; Sangeeta Gupta; Usha Manaktala; Nita Khurana (Wolters Kluwer Medknow Publications, 2016)
Objective: To study a case series of genital malignancies coexisting with genital tuberculosis. Materials and Methods: A series of three cases with known genital malignancies were found to have coexisting genital tuberculosis on subsequent workup. Results: First case was a 45 years old lady who underwent staging laparotomy for ovarian cancer. On histopathology examination, there was coexisting tuberculosis with papillary serous carcinoma. Second case was 53 years old postmenopausal lady who underwent extrafascial hysterectomy along with pelvic lymph node dissection. Histopathology showed tubercular changes along with endometrial malignancy. Third patient was a 50 years old postmenopausal lady with stage IIA carcinoma of cervix. She underwent radical hysterectomy and histopathology revealed tubercular changes in pelvic lymph nodes. All patients were given antitubercular therapy for 9 months in postoperative period along with adjuvant therapy. Conclusion: Although diagnosed as an incidental finding in the case series, genital tuberculosis may present in patients with malignancies as a result of immunosupression.